A Digitális Egységes Piaci Stratégia szerződési jogi hatásai a magyar polgári jogra - Árva, Máté (Debreceni Jogi Műhely, 2017)
The necessity of framing contract law fulfilling the expectations of the digital era is among the main purposes of the Digital Single Market Strategy, that has been introduced by the European Committe in 2015. Within the Strategy two directive proposals have been presented: the directive of the European Parliament and of the Council on certain aspects concerning contracts for the supply of digital content and the directive of the European Parliament and of the Council on certain aspects concerning contracts for the online and other distance sales of goods. These include the concept of conformity with the contract, the meaning of which raises several questions to be answered regarding the Hungarian legal system.My treatise focuses on the investigation of the criteria of conformity with the contract with special regard to the definiton of the directive proposals. In the first place I outline the elements of conformity with the contract, then I attempt to create a comprehensive definition of it. Thereafter I analyse the rules of the Hungarian Civil Code that are connected to the category of the conformity. Furthermore, I investigate the necessity of the integration of the conformity with the contract into the the Hungarian civil law. Finally, I present a future legislative concept that could be regarded as a possible way of adaptation of this legal category.